A closed chondromimetic environment within magnetic-responsive liquified capsules encapsulating stem cells and collagen II/TGF-β3 microparticles - Correia, C. R. (2016)
TGF-β3 is enzymatically immobilized by transglutaminase-2 action to poly(l-lactic acid) microparticles coated with collagen II. Microparticles are then encapsulated with stem cells inside liquified spherical compartments enfolded with a permselective shell through layer-by-layer adsorption. Magnetic nanoparticles are electrostatically bound to the multilayered shell, conferring magnetic-response ability. The goal of this study is to engineer a closed environment inside which encapsulated stem cells would undergo a self-regulated chondrogenesis. To test this hypothesis, capsules are cultured in chondrogenic differentiation medium without TGF-β3. Their biological outcome is compared with capsules encapsulating microparticles without TGF-β3 immobilization and cultured in normal chondrogenic differentiation medium containing soluble TGF-β3. Glycosaminoglycans quantification demosntrates that similar chondrogenesis levels are achieved. Moreover, collagen fibrils resembling the native extracellular matrix of cartilage can be observed. Importantly, the genetic evaluation of characteristic cartilage markers confirms the successful chondrogenesis, while hypertrophic markers are downregulated. In summary, the engineered capsules are able to provide a suitable and stable chondrogenesis environment for stem cells without the need of TGF-β3 supplementation. This kind of self-regulated capsules with softness, robustness, and magnetic responsive characteristics is expected to provide injectability and in situ fixation, which is of great advantage for minimal invasive strategies to regenerate cartilage.